Health Care Students' Attitudes About Alcohol Consumption During Pregnancy: Responses to Narrative Vignettes - Kelly D. Coons; Shelley L. Watson; Nicole M. Yantzi; Nancy E. Lightfoot; Sylvie Larocque (SAGE Publishing, 2017)
This article explores medical, midwifery, and nurse practitioner students' attitudes about women who may consume alcohol throughout their pregnancies. Twenty-one health care students responded to a scenario-based vignette addressing alcohol consumption during pregnancy, as well as a semistructured interview, which were analyzed using Braun and Clarke's thematic analysis approach. Two primary themes related to students' attitudes concerning alcohol consumption during pregnancy were identified: (a) divergent recommendations for different women, based on perceptions of their level of education, culture/ethnicity, and ability to stop drinking; and (b) understanding the social determinants of health, including the normalization of women's alcohol consumption and potential partner violence. Health care professionals in training need further education about the risks of alcohol consumption during pregnancy and fetal alcohol spectrum disorder (FASD). In addition, health care students need training in how to engage in reflective practice to identify their own stereotypical beliefs and attitudes and how these attitudes may affect their practice.